The Role of Key Performance Indicators in Improving the Performance of Clinical Pharmacist in Hospitals - Noor Syam Sidiq Himawan; Nur Wening; Dwi Pudjaningsih; Lestari Wahyu Herawati (Institute of Medico-legal Publications Pvt Ltd, 2021)
Key performance indicators are a way to improve performance, including in the hospital sector. In this study,the hospital used was private hospital, Central Java, especially in the field of Clinical Pharmacy services. Thisresearch is motivated by the low achievement of clinical pharmacy services. The purpose of this researchis to measure the performance of the clinical pharmacy service before and after the intervention with theapplication of clinical pharmacy Key Performance Indicators (cpKPI). This study is an observational studyby observing differences in the achievement of clinical pharmacist performance indicators before and afterthe implementation of cpKPIs. This studywas conducted using clinical pharmacist visit data for all inpatientsat the hospital in September 2019-February 2020. Data analysis used a paired t-test.The use of cpKPI wasable to significantly improve the performance of clinical pharmacists (p<0.05) related to drug reconciliationindicators, drug therapy services, pharmacist participation in patient management, patient education duringhospitalization, and comprehensive direct pharmacists’ care. The result proves that cpKPI can improve theperformance of clinical pharmacists at Private hospital so that this method can be used by other hospitals toimprove the performance of clinical pharmacy services.